Early mobilisation and rehabilitation in Swiss intensive care units: a cross-sectional survey (Swiss Medical Weekly, 2022)
BACKGROUND: Patients in intensive care units (ICUs) are at high risk of developing physical, functional, cognitive, and mental impairments. Early mobilisation aims to improve patient outcomes and is increasingly considered the standard of care. This survey aimed to investigate the characteristics, current use and variations of early mobilisation and rehabilitation in Swiss ICUs. METHODS: We conducted a cross-sectional survey among all ICU lead physicians, who provided data on their institutional characteristics, early mobilisation and rehabilitation practices, and their perceptions of the use and variation of early rehabilitation practices in Switzerland. RESULTS: The survey response rate was 44% (37/84). Among ICUs caring for adults (34/37), 26 were in the German-speaking region, five in the French-speaking region, and three in the Italian-speaking region. All ICUs regularly involved physiotherapy in the rehabilitation process and 50% reported having a specialised physiotherapy team. All ICUs reported performing early mobilisation, starting within the first 7 days after ICU admission. About half reported the use of a rehabilitation (45%) or early mobilisation protocol (50%). Regular, structured, interdisciplinary rounds or meetings of the ICU care team to discuss rehabilitation measures and goals for patients were stated to be held by 53%.The respondents stated that 82% of their patients received early mobilisation measures during their ICU stay. Most frequently provided mobilisation measures included passive range of motion (97%), passive chair position in bed (97%), active range of motion muscle activation and training (88%), active side to side turning (91%), sitting on the edge of the bed (94%), transfer from bed to a chair (97%), and ambulation (94%). The proportion of ICUs providing a specific early mobilisation measure, the proportion of patients receiving it, and the time dedicated to it varied across language regions, hospital types, ICU types, and ICU sizes.Almost one third of the ICU lead physicians considered early rehabilitation to be underused in their own ICU and about half considered it to be underused in Switzerland more generally. ICU lead physicians stressed lack of personnel, financial resources, and time as key causes for underuse. Moreover, they highlighted the importance of early and systematic or protocol-based rehabilitation and interprofessional approaches that are adaptive to the patients' rehabilitation needs and potential. CONCLUSION: This survey suggests that almost all ICUs in Switzerland practice some form of early mobilisation with the aim of early rehabilitation. However, the described approaches, as well as the reported use of early mobilisation measures were heterogenous across Swiss ICUs.